Download or stream? Steal or buy? Developing a typology of today's music consumer. Issue 1 (11th August 2015) - Sinclair, Gary; Green, Todd
Abstract: This paper explores the impact that recent transformations in digital music technology (e.g. the increasing popularity of legal streaming platforms) have had on the consumer experience. Following 35 in‐depth qualitative interviews, we have identified four key segments of contemporary music consumers (steadfast pirates, ex‐downloaders, mixed tapes and the old schoolers [the disengaged]) based on a continuum of their preference for illegal music piracy. Examining key themes (e.g. morality, format, value and identity investment) to distinguish each segment, we contribute to a fragmented music piracy literature in particular through the identification of the "ex‐downloaders" and "mixed tape" segments. Previous literature has tended to frame music piracy in very simplistic terms, failing to acknowledge a large number of consumers who are conflicted about their actions and rationalise their piracy in complicated and inconsistent ways related to the broader industry and their own sense of identity as a music consumer. Additionally, the discussion of the ex‐downloader segment provides significant evidence that for a large number of consumers, a policy of participation, in the shape of providing superior alternatives for legal digital music consumption, can be much more beneficial in tackling the problem of piracy than previous strategies of policing and coercion. Managerial and future research implications are discussed. Copyright © 2015 John Wiley & Sons, Ltd.